Factors influencing the success of small-scale irrigation farmers in Nkomazi (Mpumalanga) - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Dissertation (MSc (Agricultural Extention))--University of Pretoria, 2003.